Development of Ordered, Porous (Sub-25 nm Dimensions) Surface Membrane Structures Using a Block Copolymer Approach - Ghoshal, Tandra; Holmes, Justin D.; Morris, Michael A. (Scientific reports, 2018)
In an effort to develop block copolymer lithography to create high aspect vertical pore arrangements in a substrate surface we have used a microphase separated poly(ethylene oxide) -b- polystyrene (PEO-b-PS) block copolymer (BCP) thin film where (and most unusually) PS not PEO is the cylinder forming phase and PEO is the majority block. Compared to previous work, we can amplify etch contrast by inclusion of hard mask material into the matrix block allowing the cylinder polymer to be removed and the exposed substrate subject to deep etching thereby generating uniform, arranged, sub-25 nm cylindrical nanopore arrays. Briefly, selective metal ion inclusion into the PEO matrix and subsequent processing (etch/modification) was applied for creating iron oxide nanohole arrays. The oxide nanoholes (22 nm diameter) were cylindrical, uniform diameter and mimics the original BCP nanopatterns. The oxide nanohole network is demonstrated as a resistant mask to fabricate ultra dense, well ordered, good sidewall profile silicon nanopore arrays on substrate surface through the pattern transfer approach. The Si nanopores have uniform diameter and smooth sidewalls throughout their depth. The depth of the porous structure can be controlled via the etch process.